Lethal and Sublethal Effects of Ingested Hydroprene and Methoprene on Development and Fecundity of the Common Bed Bug (Hemiptera: Cimicidae). Issue 4 (26th February 2020) - Sierras, Angela; Schal, Coby
Abstract: In the last two decades, bed bugs ( Cimex lectularius L. and Cimex hemipterus F.) have become perennial and difficult to control indoor pests. Current pest control options are severely constrained by high prevalence of insecticide resistance and availability and relatively high costs of alternative interventions. Among various measures to counter the drawbacks of insecticide resistance include efforts to diversify the modes of action of insecticides with residual applications of combinations of insecticides, which include a juvenile hormone analog (JHA). JHAs, such as hydroprene and methoprene, have a desirable safety profile and are effective against a variety of indoor pests. We evaluated the potential of hydroprene and methoprene to be incorporated into an ingestible bait, with dose–response studies on fifth-instar male and female bed bugs. Females were more susceptible than males to both JHAs, and methoprene was more effective by ingestion than hydroprene at inducing both lethal and sublethal effects. Ingestion of ≥10 µg/ml blood of either JHA by last instar nymphs reduced oviposition; untreated females that mated with males exposed to high concentrations of either JHA also exhibited lower oviposition. We suggest that methoprene could be incorporated into integrated pest management programs in liquid baits and residual sprays in combination with other active ingredients.